The Effect of the Cooperative Learning Model of Make a Match Type Assisted By Food Chain Puzzle Media (Purama) on Science Learning Outcomes - Amalia, Rizka Afni; Sukmarani, Dhuta; Mardiana, Tria (Universitas Sang Bumi Ruwa Jurai, 2024)
This study aims to determine the effect of the cooperative learning model of the Make A Match type assisted by the food chain puzzle media (Purama) on science learning outcomes in fifth grade students at SD Negeri 3 Plososari, Kendal Regency. This research uses the type of research Pre-Experimetal Design with the type of One Group Pretest-Posttest Design. The samples taken were 26 students who were used as experimental classes. The sampling technique uses total sampling. Data collection used the test method in the form of 30 multiple choice questions. This test was used to determine the ability of student learning outcomes in ecosystem material before and after being given treatment. The analysis used in this study used the Paired Sample T-Test with the help of SPSS version 25.0 for windows. The results showed that the cooperative learning model of the Make A Match type assisted by Purama media had an effect on science learning outcomes in fifth grade students at SD Negeri 3 Plososari, Kendal Regency.